If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(u + -6) = -3u + 42 Reorder the terms: -9(-6 + u) = -3u + 42 (-6 * -9 + u * -9) = -3u + 42 (54 + -9u) = -3u + 42 Reorder the terms: 54 + -9u = 42 + -3u Solving 54 + -9u = 42 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. 54 + -9u + 3u = 42 + -3u + 3u Combine like terms: -9u + 3u = -6u 54 + -6u = 42 + -3u + 3u Combine like terms: -3u + 3u = 0 54 + -6u = 42 + 0 54 + -6u = 42 Add '-54' to each side of the equation. 54 + -54 + -6u = 42 + -54 Combine like terms: 54 + -54 = 0 0 + -6u = 42 + -54 -6u = 42 + -54 Combine like terms: 42 + -54 = -12 -6u = -12 Divide each side by '-6'. u = 2 Simplifying u = 2
| -2u+46=-7(u-3) | | 21=-3/5y | | ln(4x+5)=0 | | x^2-55x-500=0 | | 2=7(w-2)-3w | | 23s-4t-14s= | | 2=7(w-2)-3 | | Y=-0-19/2 | | 10(s-5)=-143 | | -24=3u+5(u+8) | | 7(v-6)+6v=-3 | | 7(v-6)+6v=3 | | a(2a-3b)= | | -36=8(x+3)-2x | | (2a-3ab)-(4a+5b)= | | 2(4s+1)=10 | | -6=-6y+3(y-4) | | 7(2l+6)=168 | | 2v/3=6 | | 5(a-6)=35 | | 4u=16/5 | | 3x+1+12.5=15 | | v=5-(4t/3) | | (q-7)*6=60 | | Z+3y=2z+y | | 22c-4c=36 | | (5b^3+8b^2-8)+(2B^3-8b+9)= | | a+a-36=70 | | 3w^6+4w^4-6w^2-8=0 | | 12z-3z= | | 1+2x=2x+2 | | Y=15(0)-5 |